2023
DOI: 10.3390/coatings13071177
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Edible Films and Coatings for Fruits and Vegetables

Anuradhi Liyanapathiranage,
Rohan S. Dassanayake,
Ashoka Gamage
et al.

Abstract: As a novel post-harvesting strategy, edible films and coatings for fruits and vegetables offer preservation measures to meet the growing needs of hunger and agricultural management. The functionality of edible films and coatings is distinctly the same. However, edible films and coatings differ in their processing and physicomechanical characteristics as they are designed to improve the shelf life, barrier, and nutritional properties of the food. With emerging concerns about sustainability, biomacromolecules ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 275 publications
0
9
0
Order By: Relevance
“…Additionally, this polymer can form a colorless, odorless, nontoxic, stable, and uniform coating, although it sometimes lacks sufficient mechanical strength [ 13 ]. To address this, recent studies have highlighted the potential of blending polymers to bolster the coating’s strength and prevent fruit quality loss [ 14 ]. Gelatin (Gel), a protein-based edible polymer, has gained popularity due to its biodegradable attributes and superior film and coating formation capabilities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this polymer can form a colorless, odorless, nontoxic, stable, and uniform coating, although it sometimes lacks sufficient mechanical strength [ 13 ]. To address this, recent studies have highlighted the potential of blending polymers to bolster the coating’s strength and prevent fruit quality loss [ 14 ]. Gelatin (Gel), a protein-based edible polymer, has gained popularity due to its biodegradable attributes and superior film and coating formation capabilities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, edible coatings and biodegradable packaging are safe and environmentally friendly packaging systems; they are made from natural substances such as pectin, chitosan, or sodium alginate to maintain quality and extend the shelf life of mushrooms [32][33][34][35][36], and are mostly composed of active ingredients with antibacterial and antioxidant activities [37,38]. Studies have shown that the incorporation of essential oils, active ingredients, and nanoparticles in edible coatings and biodegradable film packaging can improve the techno-functional properties of the packaging materials [39].…”
Section: Introductionmentioning
confidence: 99%
“…Edible coatings (ECs) are a promising technology used to improve the quality, safety, shelf life, and overall consumer appeal of various ready-to-eat fruits [25]. These coatings, typically made from natural polymers such as proteins, polysaccharides, lipids, or combinations thereof, form a protective layer on the surface of the fruit that helps to prolong the fruit's shelf life and marketability.…”
Section: Introductionmentioning
confidence: 99%